ASSESSMENT OF DYNAMICS OF HEMOSTASIS SYSTEM INDICATORS AND INFLAMMATION MARKERS IN PATIENTS WITH CORONAVIRUS INFECTION - Nabiyeva Farangiz Sadriddinovna; Musayeva Firuza Ravshanovna (Western European Studies, 2024)
The coronavirus infection (COVID-19) is an infectious disease that spreads rapidly all over the world and is accompanied by severe complications. Severe coagulopathy, arterial and venous thrombosis were the main causes of death in COVID-19. In addition, it was noted that the indicators of acute phase proteins in patients increased several times over the standard indicators. Inflammatory reaction, which is evident in response to coronavirus infection, can damage the blood vessel wall and lead to the activation of the hemostasis system [1,3,7,10,14].
Keywords: coronavirus; COVID-19; hemostasis; D-dimer